7.7k views
3 votes
Solve each system by substitution

Solve each system by substitution-example-1
User Somdoron
by
5.8k points

2 Answers

2 votes

\left \{ {{-3x-3y=3\:(I)} \atop {y=-5x-17\:(II)}} \right.
Replace the equation y in the first equation.

-3x-3y=3 (I)

-3x-3*(-5x-17)=3

-3x+15x+51=3
Now, put the numbers with letter (incognito) to the right and numbers without letter to the left, changing the signal when changing sides.

-3x+15x=3-51

12x = -48

x = (-48)/(12)

\boxed{\boxed{x = - 4}}\end{array}}\qquad\quad\checkmark


Now substitute the found value "x" in the equation y (second equation):

y=-5x-17\:(II)

y = - 5*(-4) - 17

y = 20 - 17

\boxed{\boxed{y=3}}\end{array}}\qquad\quad\checkmark

Answer:

\underline{\textbf{The\:values\​\:found\:are:\:X = -4\:and\: Y = 3} }

User Buntylm
by
5.6k points
2 votes
-3x-3y=3
y=-5x-17----------use this to substitute for y

-3x-3(-5x-17)=3----------like this
-3x+15x+51=3-------------combine like terms
12x+51=3------------subtract 51 both sides
12x=-48---------divide by 12 each side to get x by itself
x=-4

y=-5(-4)-17--------------------substitute the -4 for x to find y
y=3

now we plug in both to see if it works:
-3(-4)-3(3)=3--------------We plug in to see if both answers work
12-9=3----------------It works
(-4,3)

Hope this helps :)
User Shalisha
by
5.1k points